OCT-guided Robotic Subretinal Needle Injections: A Deep Learning-Based Registration Approach - Mach, Kristina; Wei, Shuwen; Kim, Ji Woong; Martin-Gomez, Alejandro; Zhang, Peiyao; Kang, Jin U.; Nasseri, M. Ali; Gehlbach, Peter; Navab, Nassir; Iordachita, Iulian (Proceedings - 2022 IEEE International Conference on Bioinformatics and Biomedicine, BIBM 2022, 2022)
Subretinal injection (SI) is an ophthalmic surgical procedure that allows for the direct injection of therapeutic substances into the subretinal space to treat vitreoretinal disorders. Although this treatment has grown in popularity, various factors contribute to its difficulty. These include the retina's fragile, nonregenerative tissue, as well as hand tremor and poor visual depth perception. In this context, the usage of robotic devices may reduce hand tremors and facilitate gradual and controlled SI. For the robot to successfully move to the target area, it needs to understand the spatial relationship between the attached needle and the tissue. The development of optical coherence tomography (OCT) imaging has resulted in a substantial advancement in visualizing retinal structures at micron resolution. This paper introduces a novel foundation for an OCT-guided robotic steering framework that enables a surgeon to plan and select targets within the OCT volume. At the same time, the robot automatically executes the trajectories necessary to achieve the selected targets. Our contribution consists of a novel combination of existing methods, creating an intraoperative OCT-Robot registration pipeline. We combined straightforward affine transformation computations with robot kinematics and a deep neural network-determined tool-tip location in OCT. We evaluate our framework's capability in a cadaveric pig eye open-sky procedure and using an aluminum target board. Targeting the subretinal space of the pig eye produced encouraging results with a mean Euclidean error of 23.8μm.
CRIS-Team Scopus Importer:2023-03-08